2013
DOI: 10.1097/sla.0b013e318288ea96
|View full text |Cite
|
Sign up to set email alerts
|

Gut-Associated Biomarkers L-FABP, I-FABP, and TFF3 and LIT Score for Diagnosis of Surgical Necrotizing Enterocolitis in Preterm Infants

Abstract: The LIT score can effectively differentiate surgical NEC from nonsurgical NEC infants and nonsurvivors of NEC from survivors at the onset of clinical presentation. Frontline neonatologists and surgeons may, therefore, target NEC infants who are most in need of close monitoring and those who may benefit from early surgical intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
1
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(104 citation statements)
references
References 25 publications
2
79
1
6
Order By: Relevance
“…In the present study we obtained samples of plasma and urine in regular intervals of 8 h. This method is in contrast to other publications, in which analyses of single, daily or 24-hour samples of plasma and/or urine are reported [2,4,5,12,13,14,19,20,21], with the one exception being the study of Edelson et al [3]. The obvious advantage is gaining an insight into the clinical course of the disease and associated I-FABP levels.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In the present study we obtained samples of plasma and urine in regular intervals of 8 h. This method is in contrast to other publications, in which analyses of single, daily or 24-hour samples of plasma and/or urine are reported [2,4,5,12,13,14,19,20,21], with the one exception being the study of Edelson et al [3]. The obvious advantage is gaining an insight into the clinical course of the disease and associated I-FABP levels.…”
Section: Discussionmentioning
confidence: 57%
“…This gives the clinician the opportunity to select the best possible way to measure I-FABP. Although several studies report on I-FABP measured in plasma [3,4,19] and serum [20], and several others on the use of urinary I-FABP measurements [5,12,13,14], no literature compares both methods. Several positive and negative aspects of both measuring methods can be identified.…”
Section: Discussionmentioning
confidence: 99%
“…C-reactive protein, white blood cell and platelet counts have been used quite commonly, but these do not specifically represent NEC if they are abnormal [54]. Biomarkers for diagnosis under study include intestinal fatty acid-binding protein, claudin 3, calprotectin and IL-8 [54,55,56,57]. Use of these appears to be promising, but exactly how they will be utilized in the clinical setting remains to be seen.…”
Section: Diagnostic Considerationsmentioning
confidence: 99%
“…Studies have indicated that the scores for neonatal acute physiology-perinatal extension-II and metabolic derangement acuity were insufficient measures for deciding on surgical treatment for the patients affected by NEC (8). A study from Hong Kong found that the intestinal trefoil factor (ITF) 3 level was higher in NEC patients than in non-NEC patients, suggesting that NEC affects ITF production (9). ITF is a member of the trefoil family and may protect the mucosa from insult, stabilize the mucus layer, and affect healing of the epithelium (10).…”
Section: Introductionmentioning
confidence: 99%